1984
DOI: 10.1002/bip.360230723
|View full text |Cite
|
Sign up to set email alerts
|

Azobenzene‐Containing polypeptides: Photoregulation of conformation in solution

Abstract: SynopsisPhotochromic polypeptides, with 16 to 56% azobenzene groups in the side chains, have been prepared by reaction of poly(L-glutamic acid) with paminoazobenzene, both in the presence of dicyclohexylcarbodiimide/N-hydroxybenzotriizole and of pivaloyl chloride. Analogous modification reactions carried out on polyk-aspartic acid) were unsuccessful owing to the formation of N-succinimide rings. In trimethylphosphate, all the azopolypeptides exhibit the a-helix CD pattern. Irradiation produces the tram-tocis i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

1987
1987
2011
2011

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 57 publications
(27 citation statements)
references
References 32 publications
0
27
0
Order By: Relevance
“…Irradiation induces a conformational transition from the random coil to the a-helical structure. [7] Furthermore, polyA C H T U N G T R E N N U N G (l-lysine) appended with azobenzene chromophores has been shown to transform from a b-sheet structure to an a-helix structure upon photoisomerization. [8] The remarkable conformational transitions in all of these cases were found to be strongly dependent on the polymers environment and employed solvent mixtures and hence were attributed to the changes in the polarity of the photochromic side chains affecting the surrounding media.…”
Section: Introductionmentioning
confidence: 99%
“…Irradiation induces a conformational transition from the random coil to the a-helical structure. [7] Furthermore, polyA C H T U N G T R E N N U N G (l-lysine) appended with azobenzene chromophores has been shown to transform from a b-sheet structure to an a-helix structure upon photoisomerization. [8] The remarkable conformational transitions in all of these cases were found to be strongly dependent on the polymers environment and employed solvent mixtures and hence were attributed to the changes in the polarity of the photochromic side chains affecting the surrounding media.…”
Section: Introductionmentioning
confidence: 99%
“…The polymers were obtained by treating high molecular weight poly(l-glutamic acid) with p-aminoazobenzene in the presence of dicyclohexylcarbodiimide (DCCI) and N-hydroxy-benzotriazole (HOBt). [21,22] The photochromic reactions are illustrated in Figure 3. When the modification reaction was carried out in the presence only of 13 DCCI, the modified polymers were found to contain considerable amounts of N-acylureic groups originating from side reactions between DCCI and the c-carboxylic acid functions.…”
Section: Azobenzene-containing Poly(l-glutamic Acid)mentioning
confidence: 99%
“…In particular, the trans-cis isomerization is characterized by a strong decrease in the intense band at about 350 nm, associated with a p-p* transition, and a concomitant intensification in the band at 450 nm, associated with the n-p* transition of the azo chromophore. [21,22] In organic solvents such as trimethylphosphate or trifluoroethanol, the azo-modified polymers show the CD pattern of the a-helix structure, with the two typical minima at 208 and 222 nm ( Figure 5). Using a 200 W lamp, irradiation for 1 or 2 minutes is enough to achieve the photostationary state.…”
Section: Azobenzene-containing Poly(l-glutamic Acid)mentioning
confidence: 99%
See 1 more Smart Citation
“…As a result, it can be estimated that the azo·S-14.1-PGA membrane changes the helix content from 76% to 46% at pH 7.5 by light. Ciardelli et al 10 reported the a-helix structure of PGA containing up to 16 mol% azobenzene groups (without sulfQnate anions) in the side chains in the solution system to be independent of the ultra-violet light irradiation at any pH. H should be emphasized, therefore, that increase in the photoPolymer J., Vol.…”
Section: Conformation Of Dark-adapted Azo · S-pga Membranementioning
confidence: 99%